Comparison Between Contact Force Monitoring and Unipolar Signal Modification as a Guide for Catheter Ablation of Atrial Fibrillation: Prospective Multi-Center Randomized Study. (August 2019) - Ejima, Koichiro; Kato, Ken; Okada, Ayako; Wakisaka, Osamu; Kimura, Ryusuke; Ishizawa, Makoto; Imai, Taku; Toyama, Yuko; Shoda, Morio; Hagiwara, Nobuhisa
Abstract : Background: Both contact force monitoring (CFM) and unipolar signal modification (USM) are guides for ablation, which improve the efficacy of pulmonary vein isolation of atrial fibrillation. We sought to compare the outcomes of atrial fibrillation ablation guided by CFM or USM. Methods: A total of 136 patients with paroxysmal atrial fibrillation underwent a circumferential pulmonary vein isolation using CF sensing ablation catheters and were randomly assigned to undergo catheter ablation guided by either CFM (CFM-guided group: n=70) or USM (USM-guided group: n=66). In the USM-guided group, each radiofrequency application lasted until the development of completely positive unipolar electrograms. In the CFM-guided group, a CF of 20 g (range, 10–30 g) and minimum force-time integral of 400 g were the targets for each radiofrequency application. The primary end point was freedom from any atrial tachyarrhythmia recurrence without antiarrhythmic drugs at 12-months of follow-up. Results: The cumulative freedom from recurrences at 12-months was 85% in the USM-guided group and 70% in the CFM-guided group ( P =0.031). The incidence of time-dependent and ATP-provoked early electrical reconnections between the left atrium and PVs, procedural time, fluoroscopic time, and average force-time integral, did not significantly differ between the 2 groups. The radiofrequency time for the pulmonary vein isolation was shorter in the USM-guided group than CFM-guided group but was not statistically significant ( P =0.077). Conclusions: USM was superior to CFM as an end point for radiofrequency energy deliveries during the pulmonary vein isolation in patients with paroxysmal atrial fibrillation in terms of the 12-month recurrence-free rate. Clinical Trial Registration: URL:https://www.umin.ac.jp/ctr/index.htm . Unique identifier: UMIN000021127.